Naturalistyczna opozycja wobec kartezjanizmu - Drozdowicz, Zbigniew (Bydgoski Oddział Polskiego Towarzystwa Filozoficznego Filo-Sofija, 2012)
NATURALISTIC OPPOSITION AGAINST DESCARTES’S THOUGHT My aim is to point out the foundations of Descartes’s programmatic antinaturalism, but also the margin left by Descartes in his program for a dialogue with the followers of naturalism. The latter used it more than once, but this opening for a dialogue was interpreted by them as Descartes’s support for naturalism. In my opinion it is not only a false interpretation of the philosopher’s intention, but also a false presentation of his views on human nature and the world that surrounds us.
Keywords: Descartes; antinaturalism; naturalism